The plot-structure of Genesis : 'will the righteous seed survive?' in the muthos-logical movement from complication to dénouement - Patterson, Todd L. (Biblical Interpretation Series, 2018)
In The Plot-structure of Genesis Todd L. Patterson argues that Genesis is organized by a development from complication to dénouement. The question 'Will the righteous seed survive?' drives the narrative to climax. Gen 4 sets up the complication. Cain and Abel are the seed of the woman who should lead humanity back to God's creation-sanctuary. Because Cain does not master sin, his unrighteousness threatens the survival of the seed. Each narrative tôlĕdôt division develops this theme until dénouement in the Joseph narrative when God ensures the survival of the promised seed. By showing how plot integrates with the widely recognized tôlĕdôt structure, prominent motifs, and enigmatic features of the text, Todd L. Patterson provides a surprisingly novel interpretation of Genesis.